The methodology of resistance training is crucial for improving short-medium distance front crawl performance in competitive swimmers: a systematic review and meta-analysis - Jin, Guoli; Jin, Yangqin; Zhang, Haoyang; Fu, Xueying; Yang, Yong; Lin, Shu-Cheng (Frontiers in Physiology, 2024)
Background: Resistance training is often a part of the routine training regimen for competitive swimmers. However, due to the variety of resistance training methodology, the results can be inconsistent and sometimes unsatisfactory. Clear recommendations are still lacking at present. Aims：(1) Quantify the impact of resistance training on swimmers' upper limb maximum strength, front crawl performance and key technical parameters; (2) Find out the key technical parameters for improving front crawl performance-stroke rate or length; (3) Through subgroup analysis determine the best methodology of resistance training to enhance the front crawl. Methods: Systematic search in the PubMed, Embase, and Web of Science databases. Meta-analyses using the inverse-variance are performed to compare swimmers' upper limb maximum strength, front crawl performance and key technical parameters in resistance training and habitual aquatic training. A subgroup analysis was performed to examine whether the results were affected by the methodology of resistance training. Results: Thirteen studies (267 competitive swimmers) met the inclusion criteria. The results of meta-analysis showed that resistance training significantly improved upper limbs maximum muscle strength, and 25, 50, 100 and 200m front crawl performance in competitive swimmers. And improvements in swimming performance may simply resulted from resistance training increasing stroke rate rather than stroke length. In addition, the results of subgroup analysis showed that only concurrent resistance training (CRT) and power training (PT) ultimately improved swimming performance by increasing the maximum muscle strength of the upper limbs.Resistance training significantly enhances competitive swimmers' upper limb strength and front crawl performance across various distances. The improvement in performance is likely attributed to an increased stroke rate rather than stroke length.In addition, CRT and PT are particularly effective, indicating the importance of selecting the appropriate methodology of resistance training for optimal swimming performance enhancement.